Synthesis of edge-site selectively deposited Au nanocrystals on TiO2 nanosheets: An efficient heterogeneous catalyst with enhanced visible-light photoactivity. (1st September 2018) - Anwer, Shoaib; Bharath, G.; Iqbal, Shahid; Qian, Hongmei; Masood, Tariq; Liao, Kin; Cantwell, Wesley J.; Zhang, Jiatao; Zheng, Lianxi
Abstract: As a result of their particular electronic structure [ nd 10 (n + 1)s 1 ] and size sensitive tunable photoresponse properties, nanocrystals of Au on a transition metal oxide support are potential candidates for use in heterogeneous photocatalysis to improve their photocatalytic activities in visible light. In the present work, by taking advantage of well-defined anatase TiO2 nanosheets with highly active (001) facets exposure as a support, we have successfully prepared randomly-deposited Au/TiO2 nanosheets nanostructures. Furthermore, with the help of a precise position-controlled synthesis strategy, we have transformed these randomly-deposited Au/TiO2 nanosheets into novel edge-site deposited Au/TiO2 nanosheets with enhanced crystalline interface contact. A noticeable dependence on Au positioning on the surface of TiO2 nanosheets for photocatalytic Rhodamine B degradation activity was identified. This remarkably enhanced photocatalytic activity of edge-site deposited Au/TiO2 nanosheets can be attributed to the synergistic effect between the Au nanocrystals and its intimate interfacial contact with TiO2 nanosheets having (001) facet exposure, which greatly improved the separation rate of the photogenerated carriers. Interestingly, from the photocurrent response measurements, it was found that the edge-site deposited Au/TiO2 nanosheets showed significantly enhanced visible photocurrent response activity compared to the randomly-deposited Au/TiO2 nanosheets. We believe that the proposed strategy, based on engineering the position of Au nanocrystals on TiO2 nanosheets, will encourage further interest in the development of high-performance wide bandgap semiconductor photocatalysts under visible light. Graphical abstract: Image 1